Design and Analysis Gires-Tournois-Interferometer Mirrors - Amer B.Dheyab; Gaillan H. Abdullah; Haider Y. Hammod; Ali Hassan (Institute of Advanced Engineering and Science, 2014)
We report the implementation and operation of GTI with high-reflectivity negative-dispersion dielectric mirrors for use in tunable ultrafast laser systems. The mirror structure is divided into two distinct regions: an underlying high-reflectivity dielectric quarter-wavelength stack and an overlying negative-dispersion section consisting of only a few layers and forming simple multiple Gires–Tournois interferometers. The example that we present was designed two structures with different spacers for operation from 670-860 nmand680-840nm has a near-constant group-delay dispersion of ±3000fs2and a peak reflectivity greater than 98%. We can usingand application of these mirrors in a mode-locked Ti: Sapphire laser.